2021
DOI: 10.48550/arxiv.2102.00731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Flare and Warp of the Young Stellar Disk traced with LAMOST DR5 OB-type stars

Yang Yu,
Hai-Feng Wang,
Wen-Yuan Cui
et al.

Abstract: We present analysis of the spatial density structure for the outer disk from 8−14 kpc with the LAMOST DR5 13534 OB-type stars. We discover the clear and similar flaring signatures beyond 8 kpc for which the scale height is from 0.14 to 0.5 kpc in the north and south side, implying that the flaring is possibly symmetrical in the Milky Way disk. We reveal that the thickness of the OB stellar disk is similar with our previous thin disk traced by red giant branch stars, possibly implying that secular evolution is … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…For instance, López-Corredoira et al (2002) found a strong flare beginning well inside R 0 based on 2MASS red clump giants. To the contrary, López-Corredoira & Molgó (2014) and Yu et al (2021) found that the flare begins at R 10 kpc by using samples of SDSS-SEGUE F8V-G5V stars and LAM-OST OB stars respectively. In recent studies, the flaring of a disk has been detected not only for our home galaxy but also for the external galaxies (Borlaff 2016;Pinna et al 2019;Kasparova et al 2020), which means that a flared disk could be a common structure in disk galaxies.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, López-Corredoira et al (2002) found a strong flare beginning well inside R 0 based on 2MASS red clump giants. To the contrary, López-Corredoira & Molgó (2014) and Yu et al (2021) found that the flare begins at R 10 kpc by using samples of SDSS-SEGUE F8V-G5V stars and LAM-OST OB stars respectively. In recent studies, the flaring of a disk has been detected not only for our home galaxy but also for the external galaxies (Borlaff 2016;Pinna et al 2019;Kasparova et al 2020), which means that a flared disk could be a common structure in disk galaxies.…”
Section: Discussionmentioning
confidence: 96%
“…Warps in stellar disc of galaxies were first discovered by van der Kruit & Searle (1981). Large surveys of galaxies have since then shown that stellar warps are present in 40 to 75% of galaxies, depending on the nature of the sample (Reshetnikov & Combes 1998;Ann & Park 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, disc heating and warping may happen simultaneously. Indeed, the outskirts of the MW's disc seem to be both flaring (e.g., Amôres et al 2017;López-Corredoira et al 2018;Thomas et al 2018) and warping (e.g., Chen et al 2019;Yu et al 2021). Khachaturyants et al (2021) suggested that settled warp stars may contribute to the flaring of the youngest stellar populations observed at large galactocentric radii in the MW.…”
Section: Introductionmentioning
confidence: 99%